Open Sesame! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Two new sesame hybrids, sesim 1 and 2, that are drought resistant, richer in oil content than local varieties, fast maturing and unlikely to bend in wind or shatter as local varieties do are being released by Uganda s Serere Agricultural Research...